Smart Materials Enabled with Artificial Intelligence for Healthcare Wearables (Adv. Funct. Mater. 51/2021). (16th December 2021) - Zheng, Youbin; Tang, Ning; Omar, Rawan; Hu, Zhipeng; Duong, Tuan; Wang, Jing; Wu, Weiwei; Haick, Hossam
Abstract : Healthcare Wearables In article number 2105482, Weiwei Wu, Hossam Haick, and co‐workers review recent developments in smart materials and their applications in healthcare wearables, starting from biosensing and wearable substrate materials, continuing with innovative wearable sensors for health monitoring, and ending with AI‐assisted data processing and healthcare decision‐making. The review also summarizes ongoing challenges and prospects for providing personal healthcare with AI‐assisted clinical decision support systems.